2008
DOI: 10.1007/s00705-008-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and phylogenetic analysis of the VP4 gene of human rotaviruses isolated in Paraguay

Abstract: Nucleotide and amino acid analyzes of the VP4 gene of human rotaviruses isolated both in Paraguay and worldwide were carried out in order to increase our knowledge about the complex pattern of evolution of this virus in nature. Paraguayan strains bearing the P[8] genotype were grouped in the lineages P[8]-1, P[8]-2, and P[8]-3. Regardless of the year of detection, all of the G4 and G9 strains were related to lineage P[8]-3, whereas the G1 strains were related to the three lineages detected in Paraguay; this fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…No additional insertion or deletion was present in the regions of the VP7 protein (data not shown). [Arista et al, , 2006Espinola et al, 2008] (Fig. 3) [Lopez et al, 1991] were conserved in all Korean isolates (data not shown).…”
Section: Phylogenetic Analysis Of Vp7mentioning
confidence: 71%
See 2 more Smart Citations
“…No additional insertion or deletion was present in the regions of the VP7 protein (data not shown). [Arista et al, , 2006Espinola et al, 2008] (Fig. 3) [Lopez et al, 1991] were conserved in all Korean isolates (data not shown).…”
Section: Phylogenetic Analysis Of Vp7mentioning
confidence: 71%
“…Previous sequencing and phylogenetic analysis data of the VP4 gene provides evidence of diversity within P[8] genotypes; four distinct lineages have been described [Gouvea et al, 1999;Cunliffe et al, 2001;Arista et al, 2005Arista et al, , 2006Ansaldi et al, 2007;Espinola et al, 2008]. Furthermore, genotype P[8] has been found to have undergone genetic and antigenic drift [Jin et al, 1996] Le et al, 2008].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1). According to a study by Espinola et al [26], lineage V-grouped strains have been isolated worldwide from the early 1990s through to the present.…”
Section: Figmentioning
confidence: 99%
“…Therefore, it is important to determine if amino acid differences between lineages can affect the reactivity of antibodies generated following natural rotavirus infections. In this report, all field isolates grouped to the P[8]-3 lineage, which is considered the most prominent lineage throughout the world (Ansaldi et al, 2007;Araujo et al, 2007;Rahman et al, 2007;Espínola et al, 2008). We also tested serum from rotavirus-infected children for reactivity against the VP8* subunit of the prototype human rotavirus strain Wa (P[8]-1 lineage) that is similar to the Rotarix vaccine licensed in Mexico since 2004 (Cheuvart et al, 2009).…”
Section: Discussionmentioning
confidence: 99%